Дослідження еквівалентності струмів лінійного трансформатора вхідному і вихідному струмам його схеми заміщення - Придубков, П.Я.; Хоменко, І.В. (Електротехніка і електромеханіка, 2011)
It is shown that linear transformer equations can be considered as an equations set formed with a loop-current method if winding currents are considered as loop currents. It is shown that the given set corresponds to the same transformer equivalent circuit with removed magnetic coupling as the one developed earlier. It is proven that the equivalent circuit input and output currents are equal to the linear transformer input and output currents, correspondingly.